A meeting of the minds : the Massey College story - Grant, Judith Skelton (Book collections on Project MUSE., 2015)
"Opened in 1963, Massey College is a residential college for graduate students at the University of Toronto. The college was the brainchild of Vincent Massey, Canada's first native-born Governor General, who wanted to create an intellectually stimulating milieu like the one he associated with the long-established colleges of Oxford and Cambridge. Massey College's first master was the legendary Canadian novelist, playwright, and editor, Robertson Davies. Davies and his successors--Patterson Hume, Ann Saddlemyer, and John Fraser--fostered a dynamic community of students, scholars, and public intellectuals that thrives today under the mastership of Hugh Segal. Written by Judith Skelton Grant, A Meeting of Minds is the definitive account of the college's first fifty years, its many traditions, and the hundreds of fellows who have passed through its halls. Full of wonderful anecdotes about the college's notable fellows and alumni, this history of Massey College takes the reader into the heart of one of Canada's most important intellectual institutions."--